2009
DOI: 10.1159/000228563
|View full text |Cite
|
Sign up to set email alerts
|

Risk/Benefit Strategies Must Be Employed in the Management of Pediatric Crohn’s Disease

Abstract: Clinicians caring for children with Crohn’s disease must consider the long-term implications of therapeutic interventions and cumulative diagnostic studies in their patients whose disease duration will be measured in decades. There is evidence of the increased severity of pediatric Crohn’s disease compared to its adult counterpart, its frequent co-morbid growth disturbances, and the frequent need for aggressive medical therapies including immunomodulators and biological agents. The initial management of most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…The varying, but mostly poor, perceived palatability of oral feeds (particularly of elemental diets) seriously limits prolonged compliance and therefore impairs the delivery of the intended therapy, with withdrawal rates as high as 39% 35 . Tube feeding tends to achieve better compliance (withdrawal rates of 10%–26%) but does present its own occasional hazards 43 . Equally, EN therapy may be particularly valuable in optimizing symptom control in those with subcritical stenosis from small bowel strictures.…”
Section: Primary Therapeutic Nutrition For CDmentioning
confidence: 99%
See 1 more Smart Citation
“…The varying, but mostly poor, perceived palatability of oral feeds (particularly of elemental diets) seriously limits prolonged compliance and therefore impairs the delivery of the intended therapy, with withdrawal rates as high as 39% 35 . Tube feeding tends to achieve better compliance (withdrawal rates of 10%–26%) but does present its own occasional hazards 43 . Equally, EN therapy may be particularly valuable in optimizing symptom control in those with subcritical stenosis from small bowel strictures.…”
Section: Primary Therapeutic Nutrition For CDmentioning
confidence: 99%
“…35 Tube feeding tends to achieve better compliance (withdrawal rates of 10%-26%) but does present its own occasional hazards. 43 Equally, EN therapy may be particularly valuable in optimizing symptom control in those with subcritical stenosis from small bowel strictures.…”
Section: Primary Nutrition Therapy Vs Steroids In Adults With CDmentioning
confidence: 99%
“…Nutritional follow-up by nutritionists, gastroenterologists, and clinicians during both the phase of remission and of inflammatory activity should be considered to be of fundamental importance for IBD patients in order reduce the risk of nutritional deficiencies and malnourishment. It has been repeatedly reported that enteral feeding with an elemental diet is just as effective as corticosteroids in inducing and maintaining remission, while maintaining a healthy nutritional status [25][26][27][28][29][30][31][32][33][34]. This therapy shows that nutritional therapy is efficacious and proves that diet is a major factor in managing IBD.…”
Section: Discussionmentioning
confidence: 92%
“…A risk-benefit strategy is advised in the management of pediatric CD, with anti-TNF as monotherapy for patients at high risk for rapid disease progression. 26,27 The potential of anti-TNF to alter the natural history in pediatric CD is however still unclear. 26,28 The use of IM eventually combined with anti-TNF has been limited because of the rare but fatal occurrence of hepatosplenic T-cell lymphoma.…”
mentioning
confidence: 99%
“…26,27 The potential of anti-TNF to alter the natural history in pediatric CD is however still unclear. 26,28 The use of IM eventually combined with anti-TNF has been limited because of the rare but fatal occurrence of hepatosplenic T-cell lymphoma. 26 Risk stratification with existing tools demonstrated a reduction of complications with anti-TNF and IM treatment in patients at high risk, but no reduction in low-risk patients.…”
mentioning
confidence: 99%